MEMBANGUN AGEN PASTORAL YANG MEMPUNYAI SIKAP DAN MENTALITAS KEBERPIHAKAN KEPADA KAUM MISKIN [Sebuah Studi Teologis Praktis] - Valentinus Vitalis Jebagu (Jurnal Alternatif Wacana Ilmiah Interkultural, 2014)
Almost all bishops'conferences,chatechetical congresses and religious conggregations have made “preferential option for the pocr” on of the priorities of their resolutions.This option includes the issues of justice,liberation,peace and ecology.The question remains, however, as to how deeply this option really affected the life and spirituality of the committed Christian and of the ecclesial group like pastoral agents?The implementation of this option, according to Mr.Valens Jebagu, will be one of the acid tests of whether the christian faith willbe relevant and whether traditional churches and their institutions will survive.Option for the poor is for the Church not only realized as a political strategy but more than that an existensial choice, A.Schweitzer states it this way:"As for humankind todaythe realiztion ofthe Kingdom of God here on earth byoptioning the poor, has become a matter of survival or extinction.Option for the poor is the most powerful symbol of hope in the religious and socail histiry ofhumankind.